2017
DOI: 10.1038/ncomms15658
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring protein nanomechanics with chemical reactivity

Abstract: The nanomechanical properties of elastomeric proteins determine the elasticity of a variety of tissues. A widespread natural tactic to regulate protein extensibility lies in the presence of covalent disulfide bonds, which significantly enhance protein stiffness. The prevalent in vivo strategy to form disulfide bonds requires the presence of dedicated enzymes. Here we propose an alternative chemical route to promote non-enzymatic oxidative protein folding via disulfide isomerization based on naturally occurring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 81 publications
0
33
0
Order By: Relevance
“…Similarly, binding of vinculin to α-catenin also requires mechanical unfolding, making the binding site accessible for binding ( 41 ). From the mechanochemistry perspective, force-exposure of structurally buried disulfide bonds or reactive side chains triggers a variety of posttranslational modifications that regulate protein folding and elasticity ( 42 , 43 ). Here, we add chaperone binding to mechanically exposed cryptic sequences as a key regulator of mechanical folding.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, binding of vinculin to α-catenin also requires mechanical unfolding, making the binding site accessible for binding ( 41 ). From the mechanochemistry perspective, force-exposure of structurally buried disulfide bonds or reactive side chains triggers a variety of posttranslational modifications that regulate protein folding and elasticity ( 42 , 43 ). Here, we add chaperone binding to mechanically exposed cryptic sequences as a key regulator of mechanical folding.…”
Section: Discussionmentioning
confidence: 99%
“…Cys8 . [a] Data for pK a values are taken from references [25,[40][41][42][43].Different pK a values for the same compound from different studies are included.…”
Section: Resultsmentioning
confidence: 99%
“…In general, in-vivo reformation of disulfide bonds is typically catalyzed by dedicated enzymes 50 , 51 , often employing the low p K a value of the catalytic cysteine as a general mechanism to foster reactivity 52 . However, other non-enzymatic oxidative pathways are slowly coming to light, involving sulfenic acid 40 , 53 or small thiols 54 , 55 , such as the ones studied here. In this vein, our experiments revealed that reducing the disulfide bonds by poor nucleophiles leads to unstable and reactive mixed disulfide products that can readily condense with the neighboring protein thiolate to form a stiff disulfide bond, yielding a properly refolded and mechanically rigid protein form.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the solvent-exposed mixed disulfide bond can react with free thiols in solution (Supplementary Fig. 25 ), yielding a fully reduced protein that can refold into a native conformation that exhibits intermediate mechanical properties between the compliant, misfolded protein and the stiff, fully oxidized form 54 . The proportion of refolded yet reduced protein experimentally measured in the presence of each distinct thiol nucleophile follows surprisingly well thermodynamic considerations based on DFT calculations of the mixed disulfide and the thiol/cysteine homodimers (Methods, and Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%